Ethno-religious Sentiments and the Need for Restructuring in Nigeria - Udeagha, Nduka; Nwamah, Grace (Advances in Social Sciences Research Journal, 2020)
Ethno-religious sentiments in Nigeria have remained incapacitating threats to peace, security and the avowed resolve of the state to exist as one indissoluble nation. Nigeria as a heterogeneous and pluralistic state is divided along ethnic and religious lines. Some people who champion conservative elements adopt ethno-religious considerations as persuasive socio-political opium. They vigorously embrace and endorse nepotistic proclivities which tend to polarize the Nigerian state and make governance, development, and unity of purpose appallingly problematic. Recurring mistrusts and prejudices between ethnic nationalities and faiths have stunted growth and stifled development in the Federal Republic of Nigeria. As its methodology to investigating ethno-religious sentiments in Nigeria and the need for restructuring, the study relies on content analysis. What is basically and structurally affecting the entity is the incongruousness of her diverse ethno-religious constituents. There is need for structural and mindset adjustments that will result in healthy competitiveness and expectedly, harness the diverse potentials and usher a new era of socio-economic development. The paper surmises that restructuring is imperative in Nigeria because it will help to cushion the palpable effects of ethno-religious sentiments that have remained the bane of a corporate Nigeria and national development.